Improved production of 5-hydroxymethylfurfural in acidic deep eutectic solvents using microwave-assisted reactions - Morais, Eduarda S. (2022)
Hydroxymethylfurfural (5-HMF) is a key platform chemical, essential for the production of other chemicals, as well as fuels. Despite its importance, the production methods applied so far still lack in sustainability. In this work, acidic deep eutectic solvents (DES), acting both as solvent and catalyst, were studied for the conversion of fructose into 5-HMF using microwave-assisted reactions. These solvents were screened and optimized by varying the hydrogen bond donor (HBD) and hydrogen bond acceptor (HBA). The bio-based solvent γ-valerolactone (GVL) was also applied as additive, leading to a boost in 5-HMF yield. Then, a response surface methodology was applied to further optimize operating conditions, such as reaction time, temperature and wt.% of added GVL. The highest 5-HMF yield attained, after optimization, was 82.4% at 130 °C, in 4 min of reaction time and with the addition of 10 wt.% of GVL. Moreover, a process for 5-HMF recovery and DES reuse was developed through the use of the bio-based solvent 2-methyltetrahydrofuran (2-Me-THF), allowing at least three cycles of 5-HMF production with minimal yield losses, while maintaining the purity of the isolated 5-HMF and the efficacy of the reaction media.